e-Commerce adoption in South African SMMEs - Mathe, Barney (University of the Witwatersrand, Johannesburg, 2024)
In this research study e-Commerce adoption in Small, Medium and Micro enterprises (SMMEs) in South Africa was studied. The purpose of this study was to determine the factors that constitute for a successful implementation of the e-Commerce strategy and compare this to the adoption of e- Commerce in SMMEs. The study evaluated frameworks/standards for successful e-Commerce implementation and with this evaluation a consolidated conceptual framework for the successful implementation of e-Commerce was developed. Through samples of both SMME and successful/most visited platforms, functionality and performance assessments of the platforms were conducted using the Jaccard similarity method, and time and method study. T-tests and ANOVA were conducted for performance assessments, to assess if there was a significant difference in performance between SMME and successful e-Commerce sites. Through these assessments it was found that there is a clear gap in adoption from both a functionality and performance perspective, 6 out of 7 of the successful sites had advanced to the last stage of adoption while only one SMME platform reached the last stage which is an external integration stage of the developed framework.
A research report submitted in fulfillment of the requirements for the Masters in Industrial Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; e-commerce; SMMEs; SDG-9: Industry, innovation and infrastructure